Flexible silicon nanowire and preparation method and application thereof
Through metal-assisted chemical etching and conductive carbon adhesive technology, flexible silicon nanowire water evaporation-induced power generation devices were prepared, solving the problems of rigid silicon nanowire fragility and limited carrier transmission of carbon nanomaterials, achieving high efficiency , stable electrical energy output, suitable for flexible wearable devices.
Patent Information
- Application Number
- CN202411253114.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-27
AI Technical Summary
Due to the fragility and large internal resistance of the rigid silicon nanowire array, existing water evaporation-induced power generation devices are difficult to meet the energy supply needs of flexible wearable devices, and the carrier transmission of carbon nanomaterials is limited, affecting the overall performance.
A vertically arranged silicon nanowire array of transverse defect structures was formed at designated locations through metal-assisted chemical etching method, and transferred to an external carrier to prepare flexible water evaporation-induced power generation devices, using conductive carbon glue as flexible lower electrodes and carbon The nanotube mesh grid serves as the upper electrode to form an efficient electrical performance output.
It realizes efficient and stable electrical energy output, meets the energy needs of flexible wearable devices, and significantly improves the performance of the device through three-dimensional structure and high-density nanopores.
Smart Images

Figure CN119191302A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy materials and devices, and specifically relates to a flexible silicon nanowire and a preparation method and application thereof. Background Art
[0002] Water covers 70% of the Earth's surface and forms a water cycle system by absorbing 35% of the solar energy incident on the Earth, which can absorb up to 100 trillion watts of energy [Nature Geoscience, 2012, 5: 691-696]. Therefore, if it can be effectively developed and utilized, even a small portion of the energy contained in the water on Earth can meet the current global energy demand. In recent years, a new energy conversion effect, namely hydrovoltaic power generation technology, has been generated through the strong coupling between materials and water in the form of flow, volatilization, dripping and evaporation. This emerging technology has greatly broadened the current technical capabilities of capturing water energy and brought ready-made clean electricity to self-powered wearable devices [Nature Nanotechnology, 2018, 13: 1109-1119]. Among them, thanks to the stable signal output of evaporation induced generators (EIG), and its characteristics of being not restricted by time and region and outputting electrical performance in the form of DC signals, this technology stands out in hydrovoltaic technology [Nature Nanotechnology, 2017, 12: 317-321]. In the water evaporation induced power generation device, a phase change process from liquid water to gaseous water occurs. The evaporation behavior generated by this phase change process causes the water on the solid-liquid interface to flow in the capillary channel, thereby driving the charge transfer, and then converting the environmental thermal energy in the process into sustainable electrical energy [Advanced Functional Materials, 2017, 27: 1700551]. And under environmental conditions, due to the continuous intermolecular thermal motion of liquid water, the water molecules near its surface are attracted to each other (derived from the saturated vapor pressure being higher than the moisture pressure in the air), so they have a certain ability to detach from the liquid surface, thus producing a self-evaporation phenomenon [Nature, 2000, 408: 564-567]. However, compared with bulk ionized water, the evaporation occurring on the surface of the material has a much lower concentration of ions and hydrogen bonds in water molecules, resulting in relatively poor chemical interactions between the molecules in the water vapor and the solid surface. The chemical composition of the surface material and the enhanced interaction with water vapor are essential for realizing high-performance water evaporation-induced power generation devices. One way to enhance the interaction is to use micro-nano materials with nanopores or channels to maximize the area of solid-water vapor interaction per unit volume. The surface hydrophilicity of the material is another key factor to ensure the operation of the device. Compared with bulk materials, the complex structure and simple synthesis methods of nanomaterials give them sufficient surface area and volume, thereby enhancing the ability of solid-liquid interaction.
[0003] In 2020, a water evaporation induced power generation device with a silicon nanowire array as a functional layer was proposed for the first time. The constructed water evaporation induced power generation device achieved good performance output due to the good specific surface area, hydrophilicity, carrier concentration and transmission speed of silicon nanowires. However, as a structure processed from silicon wafers, the metal-assisted wet-etched silicon nanowire array will inevitably be connected with silicon wafers as a carrier, and its related characteristics will also be masked by the characteristics of this thicker block silicon. In addition, it has the disadvantages of fragility and poor mechanical properties, which makes it inconvenient to develop related applications in the current environment where wearable devices are prevalent. Therefore, how to develop the silicon nanowire water evaporation induced power generation device into an energy supply platform with high efficiency and stable power output that meets the needs of wearable systems is a severe challenge. Summary of the invention
[0004] In the prior art, the industry generally uses carbon nanomaterials as the functional layer of water evaporation induced power generation devices, but their own large internal resistance limits the carrier transmission and causes losses to the overall performance; the rich carrier density of water evaporation induced power generation devices based on silicon nanowires ensures the construction of high-efficiency devices, but due to the presence of rigid silicon parts, the overall device is fragile. Therefore, constructing a flexible water evaporation induced power generation device based on silicon nanowire arrays is the root of achieving high-performance water evaporation induced power generation devices.
[0005] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:
[0006] This invention reports a method of using metal-assisted chemical etching to achieve a vertically arranged silicon nanowire array with a lateral defect structure at a specified position, and transfer the uniform vertically arranged silicon nanowire array to an external carrier. The metal-assisted etching of the silicon nanowire array and the formation mechanism of cracks were clarified, and the silicon nanowire device under this structure was prepared into a flexible water evaporation induced power generation device, which opened up a new path for the large-scale production of various flexible devices based on silicon nanowires (such as solar cells, water evaporation induced sensors and other devices).
[0007] The present invention provides a method for preparing flexible silicon nanowires, comprising the following steps:
[0008] S11: soaking the pre-treated silicon wafer in a silver plating solution for 45±5 seconds, and then soaking it in an etching solution for a second time to obtain a silicon nanowire array; the silver plating solution includes hydrofluoric acid, silver nitrate and water, and the etching solution includes hydrogen peroxide, hydrofluoric acid and water;
[0009] The secondary soaking method requires soaking at 20±3°C for 15±3min, 25±3°C for 5±1min, 35±3°C for 5±1min, and 40±3°C for 15±1min;
[0010] S12: rinsing and drying the silicon nanowire array in water, and then soaking in water at 75±3° C. for nearly 3 hours, and drying to obtain a silicon wafer with a silver film layer;
[0011] S13: Soaking the silver film-layered silicon wafer in an etching solution at 40±3° C. for 15±1 min to obtain a secondary etched silicon wafer;
[0012] S14: Soak the etched silicon wafer in a dilute nitric acid solution for 5±1 min, wash with water for 5±1 min, and dry to obtain the flexible silicon nanowires.
[0013] Preferably, the silicon wafer is an n-type silicon wafer with a thickness of 500±10 μm and a resistivity of 0.001-0.005 Ω·cm.
[0014] Preferably, the pre-treatment method comprises the following steps:
[0015] S21: at 150±5° C., the silicon wafer is cleaned in an acidic solution (hydrochloric acid), then cleaned in an alkaline solution (ammonia water), and dried to obtain a cleaned silicon wafer;
[0016] S22: ultrasonically cleaning the cleaned silicon wafer in an ethanol aqueous solution for 15±1 min and then drying to obtain a treated silicon wafer;
[0017] S23: treating the polished surface of the treated silicon wafer with oxygen plasma for 15±1 min, and etching with hydrofluoric acid aqueous solution for 3±1 min, to complete the pre-treatment process.
[0018] Furthermore, the acidic aqueous solution comprises water, hydrogen peroxide and hydrochloric acid in a mass ratio of 1:1:5; the alkaline aqueous solution comprises water, hydrogen peroxide and ammonia water in a mass ratio of 1:1:6.
[0019] Furthermore, in the steps S21 and S22, the drying method is nitrogen blowing.
[0020] Furthermore, in step S23, the unpolished silicon wafer surface is sealed with an acid- and alkali-resistant tape.
[0021] Furthermore, in the hydrofluoric acid aqueous solution, the concentration of the solute is 5±1 wt %.
[0022] Preferably, the length of the silicon nanowire array is 25-30 μm.
[0023] Preferably, the concentration of hydrofluoric acid in the silver plating solution is 4.80±0.5 mol·L -1 , the concentration of silver nitrate is 0.01±0.005mol·L -1; The concentration of hydrofluoric acid in the etching solution is 4.80±0.5mol·L -1 , the volume concentration of hydrogen peroxide is 3%.
[0024] Preferably, in step S12, the drying method is drying with nitrogen; in step S14, the drying method is natural drying.
[0025] The present invention also provides a flexible silicon nanowire prepared by the above preparation method.
[0026] The present invention also provides a silicon nanowire-based water evaporation induced power generation device, which has a vertical structure, with the above-mentioned flexible silicon nanowires peeled off from the silicon wafer through conductive carbon glue or other conductive polymer adhesive materials as the flexible lower electrode, and the laser-cut carbon nanotube mesh grid electrode as the upper electrode material.
[0027] The present invention proposes a simple immersion etching technology, which uses a metal-assisted wet etching technology to form horizontal cracks in silicon nanowires at designated positions during the etching process.
[0028] The present invention finds that the formation of the cracks is caused by the film stratification composed of silver particles during the water immersion process and the redistribution and reattachment of the silver particles during the subsequent wet etching process, wherein part of the silver is redistributed on the sidewalls of the silicon nanowires in the form of particles, forming local horizontal corrosion, leading to the generation of cracked silicon nanowires.
[0029] In addition, with the help of conductive carbon glue, through the existence of crack structure, the silicon nanowire array was peeled off and loaded on a flexible conductive carbon glue substrate, and finally a vertically structured water evaporation induced device was prepared, which produced a considerable and continuous open circuit voltage of more than 0.3V. Its excellent performance benefited from the advantages of the rich three-dimensional structure of the peeled silicon nanowires, which provided a large specific surface area, a high-density nanopore structure and a significant surface potential.
[0030] The technical solution of the present invention has the following advantages over the prior art:
[0031] The rigid silicon wafer substrate left after the silicon nanowire array is etched by metal-assisted wet etching technology cannot meet the needs of the increasingly flexible wearable devices. In the present invention, based on the etching mechanism of silicon nanowires, the chemical reaction of metallic silver is optimized during the etching stage, thereby manufacturing a cracked silicon nanowire array and vertically transferring it on an adhesive carrier. Thus, a new type of flexible silicon nanowire-based water evaporation-induced power generation device is constructed, and excellent electrical performance output is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Etching flow chart of crack-shaped silicon nanowires.
[0033] Figure 2 Figure 2 is a diagram of the formation mechanism of crack-shaped silicon nanowires; (a) schematic diagram of the reactions occurring at the interfaces of etching solution / silver (left) and silver / silicon (right); (b) when silver is delaminated from the silicon interface, excess silver ions are formed in the solution, causing silver particles to be deposited on the silicon wafer at the sidewalls and bottom of the silicon nanowire channel; (c) the delaminated silver film continues to be etched, causing the silicon nanowire to continue to extend.
[0034] Figure 3 These are scanning electron microscope images after the first etching, the second etching, and the magnified cracks.
[0035] Figure 4 Figure 3. Transfer of crack-loaded silicon nanowires and preparation of flexible silicon nanowire devices.
[0036] Figure 5 The top view microstructure of n-type silicon nanowires (a) and the structure of silicon nanowires after transfer (b).
[0037] Figure 6 Figure 2 shows the structure (a) and electrical output performance (b) of the flexible water evaporation-induced power generation device based on silicon nanowires.
[0038] Figure 7 A schematic diagram was prepared for the present invention. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0040] Example 1
[0041] The etching process of cracked silicon nanowires can be divided into two etching processes. Figure 1As shown, the preparation of silicon nanowire arrays begins with the preliminary preparation of silicon wafers: commercial n-type (100) silicon wafers are cut into 2cm×2cm square pieces with a thickness of 500μm and a resistivity of 0.001-0.005Ω·cm using a laser marking machine. The cut square silicon wafers are cleaned at 150°C for nearly 15 minutes with 1:1:5 deionized water, hydrogen peroxide, hydrochloric acid and 1:1:6 deionized water, hydrogen peroxide and ammonia solution. Then, they are cleaned in an ultrasonic cleaner with anhydrous ethanol and deionized water for nearly 15 minutes, and then the silicon wafers are blown dry with nitrogen. Before etching, the unpolished silicon wafer surface is sealed with acid-base resistant tape, and the polished surface is treated with an oxygen plasma machine for nearly 15 minutes to ensure the removal of organic residues, and placed in a 5% hydrofluoric acid solution for nearly 3 minutes to etch away any remaining silicon dioxide (SiO2).
[0042] Then prepare the solution: weigh 0.85g of silver nitrate powder on a weighing balance, add 375mL of deionized water and 125mL of hydrofluoric acid, and prepare the hydrofluoric acid concentration to about 4.80mol·L -1 , the concentration of silver nitrate is about 0.01 mol·L -1 Add 15±2mL of hydrogen peroxide solution to a concentration of about 4.80mol·L -1 500mL of hydrofluoric acid aqueous solution, so that the concentration of hydrogen peroxide is about 0.03mol·L -1 Etching solution. Then, etching is performed: the cleaned silicon wafer is immersed in the silver plating solution for 45 seconds to deposit silver particles on the surface of the wafer. Then the silicon wafer is immersed in the etching solution, and the silicon nanowire etching is carried out for a total of about 40 minutes from room temperature to 40°C (15 minutes at 20°C, 5 minutes at 25°C, 5 minutes at 35°C, and 15 minutes at 40°C), and a silicon nanowire array with a length of about 25-30 microns and uniform shape is prepared. After a secondary etching, the silicon wafer with a silicon nanowire structure is rinsed in deionized water and dried with nitrogen. Soak in a water bath in 75°C deionized water for 3 hours to delaminate the silver film. Subsequently, the silicon wafer is quickly dried and immediately returned to the etching solution for a second etching. Horizontal cracks are formed at the beginning of the second etching, and the growth of silicon nanowires will continue. After a period of etching, the silicon nanowire array is immersed in a dilute nitric acid solution for 5 minutes to dissolve excess silver particles, and finally rinsed with deionized water for 5 minutes. After natural drying, the silicon nanowire array will be used to prepare water evaporation induced power generation devices.
[0043] Example 2
[0044] The etching process of cracked silicon nanowires can be divided into two etching processes. Figure 1As shown, the preparation of silicon nanowire arrays begins with the preliminary preparation of silicon wafers: commercial n-type (100) silicon wafers are cut into 2cm×2cm square pieces with a thickness of 490μm and a resistivity of 0.001-0.005Ω·cm using a laser marking machine. The cut square silicon wafers are cleaned at 145°C for nearly 15 minutes with 1:1:5 deionized water, hydrogen peroxide, hydrochloric acid and 1:1:6 deionized water, hydrogen peroxide and ammonia solution. Then, they are cleaned in an ultrasonic cleaner with anhydrous ethanol and deionized water for nearly 15 minutes, and then the silicon wafers are blown dry with nitrogen. Before etching, the unpolished silicon wafer surface is sealed with acid-proof and alkali-proof tape, and the polished surface is treated with an oxygen plasma machine for nearly 15 minutes to ensure the removal of organic residues, and placed in a 5% hydrofluoric acid solution for nearly 3 minutes to etch away any remaining silicon dioxide (SiO2).
[0045] Then prepare the solution: weigh 0.8g of silver nitrate powder on a weighing balance, add 370mL of deionized water and 120mL of hydrofluoric acid, and prepare the hydrofluoric acid concentration to about 4.80mol·L -1 , the concentration of silver nitrate is about 0.01 mol·L -1 Add 13mL of hydrogen peroxide solution to a concentration of about 4.80mol·L -1 495 mL of hydrofluoric acid aqueous solution, so that the concentration of hydrogen peroxide is about 0.03 mol·L -1 Etching solution. Then, etching is performed: the cleaned silicon wafer is immersed in the silver plating solution for 40 seconds to deposit silver particles on the surface of the wafer. Then the silicon wafer is immersed in the etching solution, and the silicon nanowire etching is carried out for a total of about 40 minutes at room temperature to 37°C (15 minutes at 20°C, 5 minutes at 25°C, 5 minutes at 35°C, and 15 minutes at 40°C), and a silicon nanowire array with a length of about 25-30 microns and uniform shape is prepared. After a secondary etching, the silicon wafer with a silicon nanowire structure is rinsed in deionized water and dried with nitrogen. Soak in a water bath in 75°C deionized water for 3 hours to delaminate the silver film. Subsequently, the silicon wafer is quickly dried and immediately returned to the etching solution for a second etching. Horizontal cracks are formed at the beginning of the second etching, and the growth of silicon nanowires will continue. After a period of etching, the silicon nanowire array is immersed in a dilute nitric acid solution for 5 minutes to dissolve excess silver particles, and finally rinsed with deionized water for 5 minutes. After natural drying, the silicon nanowire array will be used to prepare water evaporation induced power generation devices.
[0046] Example 3
[0047] The etching process of cracked silicon nanowires can be divided into two etching processes. Figure 1As shown, the preparation of silicon nanowire arrays begins with the preliminary preparation of silicon wafers: commercial n-type (100) silicon wafers are cut into 2cm×2cm square pieces with a thickness of 510μm and a resistivity of 0.001-0.005Ω·cm using a laser marking machine. The cut square silicon wafers are cleaned at 155°C for nearly 15 minutes with 1:1:5 deionized water, hydrogen peroxide, hydrochloric acid and 1:1:6 deionized water, hydrogen peroxide and ammonia solution. Then, they are cleaned in an ultrasonic cleaner with anhydrous ethanol and deionized water for nearly 15 minutes, and then the silicon wafers are blown dry with nitrogen. Before etching, the unpolished silicon wafer surface is sealed with acid-base resistant tape, and the polished surface is treated with an oxygen plasma machine for nearly 15 minutes to ensure the removal of organic residues, and placed in a 5% hydrofluoric acid solution for nearly 3 minutes to etch away any remaining silicon dioxide (SiO2).
[0048] Then prepare the solution: weigh 0.9g of silver nitrate powder on a weighing balance, add 380mL of deionized water and 130mL of hydrofluoric acid, and prepare the hydrofluoric acid concentration to about 4.80mol·L -1 , the concentration of silver nitrate is about 0.01 mol·L -1 Add 17mL of hydrogen peroxide solution to a concentration of about 4.80mol·L -1 505 mL of hydrofluoric acid aqueous solution, so that the concentration of hydrogen peroxide is about 0.03 mol·L -1 Etching solution. Then, etching is performed: the cleaned silicon wafer is immersed in the silver plating solution for 50 seconds to deposit silver particles on the surface of the wafer. Then the silicon wafer is immersed in the etching solution, and the silicon nanowire etching is carried out for a total of about 40 minutes from room temperature to 43°C (15 minutes at 20°C, 5 minutes at 25°C, 5 minutes at 35°C, and 15 minutes at 40°C), and a silicon nanowire array with a length of about 25-30 microns and uniform shape is prepared. After a secondary etching, the silicon wafer with a silicon nanowire structure is rinsed in deionized water and dried with nitrogen. Soak in a water bath in 75°C deionized water for 3 hours to delaminate the silver film. Subsequently, the silicon wafer is quickly dried and immediately returned to the etching solution for a second etching. Horizontal cracks are formed at the beginning of the second etching, and the growth of silicon nanowires will continue. After a period of etching, the silicon nanowire array is immersed in a dilute nitric acid solution for 5 minutes to dissolve excess silver particles, and finally rinsed with deionized water for 5 minutes. After natural drying, the silicon nanowire array will be used to prepare water evaporation induced power generation devices.
[0049] Effect evaluation 1
[0050] The formation mechanism of cracked silicon nanowire arrays was analyzed and found to be closely related to the delamination of the silver film formed by silver particles in the second step of etching and the electrochemical reaction during the etching process. As mentioned above, the etching process of silicon nanowires consists of two pairs of redox reactions: one occurs at the interface between the silver film and the etching solution, and the other occurs at the interface between silver and silicon. At the silver / etching solution interface, the deposited silver particles are oxidized by hydrogen peroxide to form silver ions near the film composed of silver nanoparticles. Figure 2 (a).
[0051] Since silver has a stronger electronegativity than silicon, the formed silver ions are subsequently reduced to silver particles, and the formed silver nanoparticles are preferentially reduced to the silicon nanowire channels where the silver ions were previously located rather than to the surface of silicon [Advanced Science, 2019, 6: 1900522.]. At the same time, silicon is further oxidized due to the presence of hydrofluoric acid, achieving the etching of the silicon nanowires in the second step mentioned above. At this point, the thin film composed of silver nanowires has good contact with silicon, the number of silver ions produced by the oxidation reaction and the number of silver ions consumed by the reduction reaction are balanced, and the silver nanoparticles maintain a flat film structure. However, when the silver film is stratified, the area of the silver / etching solution interface increases, Figure 2 (b), thereby accelerating the rate of silver ion generation, that is, the rate of oxidation reaction. At the same time, the contact area between silver and silicon is reduced, and the number of electrons transferred from silicon to silver is reduced, thereby reducing the consumption rate of silver ions in the reduction reaction [Advanced Optical Materials, 2020, 8: 1901800]. The combination of faster oxidation reaction and slower reduction reaction leads to an excess of silver ions in the solution near the silver film. The accumulation of silver ions will undergo new reduction, allowing silver particles to be deposited, especially near the silver film (the sidewall position of the silicon nanowire) where the silver ion concentration is the highest. After etching again, the silver particles deposited on the sidewalls of the silicon nanowires will be etched horizontally through the silicon nanowires, resulting in the formation of cracks, such as Figure 2 As shown in (c), other silver particles are deposited in the silicon nanowire channel, causing the silicon nanowire to continue to be etched, and the sidewalls of the silicon nanowire formed during the second etching process are still smooth. Figure 4 The process of peeling cracked silicon nanowire arrays from bulk silicon substrates by conductive carbon paste as an adhesive flexible carrier is shown. As a surface, the pressure-sensitive adhesive containing carbon powder as a conductive filler has a resistivity of less than 5Ω·mm -2 , thus it can effectively transport electrons to serve as a flexible lower electrode for silicon nanowire-based water evaporation-induced power generation devices.
[0052] Figure 4The process of peeling cracked silicon nanowire arrays from bulk silicon substrates by conductive carbon paste as an adhesive flexible carrier is shown. As a surface, the pressure-sensitive adhesive containing carbon powder as a conductive filler has a resistivity of less than 5Ω·mm -2 , thus it can effectively transport electrons to serve as a flexible lower electrode for silicon nanowire-based water evaporation-induced power generation devices.
[0053] exist Figure 3 In the example 1, after scanning electron microscopy, it was found that the secondary etching formed a lateral structure with a crack shape, which made it possible to controllably break the silicon nanowires at specific locations and facilitated their transfer to other substrates.
[0054] At this time, the designed uniform horizontal cracks in the silicon nanowires obtained by the secondary etching weaken the connection between the silicon nanowire array layers produced after the upper and lower etchings. Under the action of shear stress, the silicon nanowires break first at the designated crack positions, promoting the separation of the upper silicon nanowire array from the silicon substrate and making it possible to transfer it evenly to the flexible substrate.
[0055] like Figure 5 As shown. On a substrate with carbon conductive tape as a flexible carrier, the silicon nanowire array maintains a high degree of vertical alignment and uniformity, avoiding the serious agglomeration of the tips of traditional silicon nanowires due to the presence of intermolecular forces during etching, such as dangling bonds and electrostatic charges on the newly formed surface. Therefore, this result further shows that the transfer of vertically aligned silicon nanowires is greatly promoted by the uniform horizontal cracks introduced during the silicon nanowire etching process.
[0056] Application Example 1
[0057] The overall device structure adopts a vertical structure to construct a flexible water evaporation induced power generation device based on a broken silicon nanowire array. Figure 6 (a). Specifically, a laser-cut carbon nanotube mesh grid electrode is used as the upper electrode material on a silicon nanowire array based on a conductive carbon glue electrode, and copper wires are led out at both ends of the electrode for easy measurement. When water droplets infiltrate the upper surface of the water evaporation-induced power generation device, a strong interaction occurs at the solid-liquid interface. Under the induction of water evaporation, due to the existence of the double layer effect and the streaming potential effect, the flow of water molecules generates a certain electrical signal of streaming potential in the entire device. At the same time, because silicon is a semiconductor material, its rich carrier concentration allows electron-hole pairs to be induced and move along with the directional water flow, ultimately producing something like Figure 6 (b) shows an open circuit voltage of 0.3 V and approximately 3.5 μA·cm -2It should be noted that the calculation of the current density is based on the area of the electrode part of the entire device that collects the signal (0.2×0.2cm 2 ), compared with previously reported flexible water evaporation-induced power generation devices, the device shows excellent output performance, which is due to the construction of a flexible three-dimensional network constructed by silicon nanowires, its high-density nanopore structure and high surface potential.
[0058] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing flexible silicon nanowires, characterized in that: The steps include: S11: soaking the pre-treated silicon wafer in a silver plating solution for 40-50 seconds, and then soaking it in an etching solution for a second time to obtain a silicon nanowire array; the silver plating solution includes hydrofluoric acid, silver nitrate and water, and the etching solution includes hydrogen peroxide, hydrofluoric acid and water; The secondary soaking method requires soaking at 17-23°C for 14-16 minutes, soaking at 22-28°C for 4-6 minutes, soaking at 32-38°C for 4-6 minutes, and soaking at 37-43°C for 14-16 minutes; S12: rinsing and drying the silicon nanowire array in water, and then soaking in water at 72-78° C. for nearly 3 hours, and drying to obtain a silver film-layered silicon wafer; S13: Soaking the silicon wafer with the silver film layered thereon in an etching solution at 37-43° C. for 14-16 minutes to obtain a secondary etched silicon wafer; S14: Soaking the etched silicon wafer in a dilute nitric acid solution for 4-6 minutes, washing with water for 4-6 minutes, and drying to obtain the flexible silicon nanowires.
2. The preparation method according to claim 1, characterized in that The silicon wafer is an n-type silicon wafer with a thickness of 490-510 μm and a resistivity of 0.001-0.005 Ω·cm.
3. The preparation method according to claim 1, characterized in that: The pre-treatment method comprises the following steps: S21: cleaning the silicon wafer in an acidic solution at 145-155° C., then cleaning in an alkaline solution, and drying to obtain a cleaned silicon wafer; S22: ultrasonically cleaning the cleaned silicon wafer in an ethanol aqueous solution for 14-16 minutes and then drying to obtain a treated silicon wafer; S23: treating the polished surface of the treated silicon wafer with oxygen plasma for 14-16 minutes and etching with hydrofluoric acid aqueous solution for 2-4 minutes to complete the pre-treatment process.
4. The preparation method according to claim 3, characterized in that: The acidic aqueous solution comprises water, hydrogen peroxide and hydrochloric acid in a mass ratio of 1:1:5; the alkaline aqueous solution comprises water, hydrogen peroxide and ammonia water in a mass ratio of 1:1:
6.
5. The preparation method according to claim 3, characterized in that: In the step S23, the unpolished silicon wafer surface is sealed with an acid- and alkali-resistant tape.
6. The preparation method according to claim 3, characterized in that: In the hydrofluoric acid aqueous solution, the concentration of the solute is 5±1 wt %.
7. The preparation method according to claim 1, characterized in that: The length of the silicon nanowire array is 25-30 μm.
8. The preparation method according to claim 1, characterized in that: The concentration of hydrofluoric acid in the silver plating solution is 4.3-5.3 mol·L -1 , the concentration of silver nitrate is 0.005-0.015 mol·L -1 ; The concentration of hydrofluoric acid in the etching solution is 4.3-5.3 mol·L -1 , the volume concentration of hydrogen peroxide is 3%.
9. A flexible silicon nanowire prepared by the preparation method according to any one of claims 1 to 8.
10. A silicon nanowire-based water evaporation induced power generation device, characterized in that: The flexible silicon nanowires described in claim 9 are peeled off from the silicon wafer through conductive carbon glue or other conductive polymer adhesive materials as the flexible lower electrode, and the laser-cut carbon nanotube mesh grid electrode is used as the upper electrode material.
